Vitamin B6 catabolism and lung cancer risk: results from the Lung Cancer Cohort Consortium (LC3). (30th January 2019) - Zuo, H; Ueland, P M; Midttun, Ø; Tell, G S; Fanidi, A; Zheng, W; Shu, X; Xiang, Y; Wu, J; Prentice, R; Pettinger, M; Thomson, C A; et al.
Abstract: Background: Increased vitamin B6 catabolism related to inflammation, as measured by the PAr index (the ratio of 4-pyridoxic acid over the sum of pyridoxal and pyridoxal-5'-phosphate), has been positively associated with lung cancer risk in two prospective European studies. However, the extent to which this association translates to more diverse populations is not known. Materials and methods: For this study, we included 5323 incident lung cancer cases and 5323 controls individually matched by age, sex, and smoking status within each of 20 prospective cohorts from the Lung Cancer Cohort Consortium. Cohort-specific odds ratios (ORs) and 95% confidence intervals (CIs) for the association between PAr and lung cancer risk were calculated using conditional logistic regression and pooled using random-effects models. Results: PAr was positively associated with lung cancer risk in a dose-response fashion. Comparing the fourth versus first quartiles of PAr resulted in an OR of 1.38 (95% CI: 1.19–1.59) for overall lung cancer risk. The association between PAr and lung cancer risk was most prominent in former smokers (OR: 1.69, 95% CI: 1.36–2.10), men (OR: 1.60, 95% CI: 1.28–2.00), and for cancers diagnosed within 3 years of blood draw (OR: 1.73, 95% CI: 1.34–2.23). Conclusion: Based on pre-diagnostic data from 20 cohorts across 4 continents, this study confirms that increased vitamin B6 catabolism related to inflammation and immune activation is associated with a higher risk of developing lung cancer. Moreover, PAr may be a pre-diagnostic marker of lung cancer rather than a causal factor.